Iron Indices in School Children in Ceres District of the Western Cape South Africa (Journal of Biomedical Investigation, 2009)
Iron status of children from communities in South Africa has been a subject of debate and the lack of single biochemical indicator makes it more challenging, hence this study was designed to assess the iron status of children in a Ceres district of the Western Cape in South Africa. For this study, 265 children were randomly recruited and blood sample collected from the participating children was used for the analysis of the following parameters; soluble transferrin receptors (sTfR), haemoglobin (Hb), mass cell volume (MCV) and ferritin (Fert). The result showed that the mean serum iron level of 13.45 umol/l, mean serum ferritin level of 1.85mg/l, mean serum transferring receptor of 30.11 ug/l were recorded in >75% of the participating children. The Haemoglobin level of less than 12.5 g/l and mass cell volume of 83.10 ft were observed in >50%, of participating children. There were no gender differences for any of the iron measure. The haemoglobin level showed marginal iron deficiency while only serum iron was significantly correlated with the haemoglobin level. The serum transferrin receptors, ferritin and MCV did not indicate possible iron deficiency. The results of other factors such as socioeconomic status and demographic data did not show any significant interference either. The implication of the finding is discussed.
Keywords: Blood; iron; children; Hb; STR; MCV; Fert